Mix proportion design method of densely-distributed elastic pavement paving mixture
By determining the optimal aggregate grading of rubber particles and calculating the mass ratio of rubber aggregate, polymer bonding materials and fillers, the problems of difficult forming and insufficient durability of rubber aggregate pavement mixture are solved, and the uniformity and durability of the mixture are improved.
Patent Information
- Application Number
- CN202510600155.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-12
- Publication Date
- 2025-06-10
- Estimated Expiration
- 2045-05-12
AI Technical Summary
The existing rubber aggregate pavement mixture has problems with forming difficulties, under-compacting degree and looseness, resulting in insufficient durability of the pavement and affecting its promotion and application.
By determining the optimal aggregate grading of rubber particles in different particle size ranges, and using the main aggregate filling method to combine volume parameters, the mass ratio of rubber aggregate, polymer bonding material and filler is calculated, and after insertion and pounding is carried out to determine the optimal powder-glue ratio of filler and polymer bonding material.
The uniformity of the mixture and the target void ratio are achieved accurately, the durability and water stability of the road surface are improved, and the problem of under-compacting test pieces caused by traditional design and molding methods is avoided.
Smart Images

Figure CN120126607A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of road engineering materials, and particularly relates to a mix proportion design method for a dense-graded elastic pavement paving mixture. Background Art
[0002] An elastic pavement is a new type of pavement mainly composed of waste tire rubber particles, polymer binders, and stones. It has excellent noise reduction performance and environmental protection characteristics. Due to its low modulus, it is often used as a functional wearing course of the pavement.
[0003] The pavement mixture prepared with waste rubber particles as aggregates has the advantages of strong elastic recovery ability, light weight, and low cost, but also has the problem of difficult mixture forming. In order to obtain good elasticity and noise reduction performance while ensuring the mixture strength, current rubber aggregate pavements are mostly prepared by traditional gradation design and forming methods. The prepared rubber aggregate pavement mixtures are mostly open-graded porous structures, and the rubber particle dosage is small, resulting in large voids in the mixture. The large void structure reduces the contact points between aggregates, reducing the overall bearing capacity and structural stiffness of the rubber aggregate pavement. Under the action of vehicle loads, larger relative displacements are more likely to occur between rubber particles, causing structural loosening and crack propagation. At the same time, the large void structure will cause water to penetrate into the interior of the pavement, accelerating the aging of the binder, reducing the adhesion between rubber particles and the binder, and further weakening the durability of the pavement.
[0004] Therefore, the rubber aggregate pavement mixtures prepared by traditional gradation design and forming methods have problems such as unqualified compaction degree and loose mixture, resulting in insufficient pavement durability, seriously affecting the popularization and application of rubber aggregate pavement mixtures. Summary of the Invention
[0005] In order to solve the above problems existing in the prior art, the present invention provides a mix proportion design method for a dense-graded elastic pavement paving mixture. The technical problems to be solved by the present invention are realized through the following technical solutions: The embodiment of the present invention provides a mix proportion design method for a dense-graded elastic pavement paving mixture, including the steps of: S1. Mix rubber particles in different particle size ranges according to different mass ratios and conduct a compacted density test to determine the minimum skeleton void ratio and the optimal mass ratio between rubber particles in different particle size ranges, and obtain the optimal aggregate gradation of rubber particles in different particle size ranges; S2. Stir the filler and the polymer binder evenly according to different powder-binder ratios to obtain several groups of binders; S3. Using the main aggregate filling method, calculate the mass ratios of rubber aggregate, polymer binder, and filler in mixtures with different powder-binder ratios according to the sum of the volumes of the binder, filler, and the volume occupied by the target air void ratio of the mixture being equal to the void volume of the aggregate skeleton, where the void volume of the aggregate skeleton is calculated from the minimum skeleton void ratio; S4. Mix the rubber particles with the optimal aggregate gradation and each group of the binder uniformly according to the mass ratios to obtain several groups of elastic pavement paving mixtures; S5. Put each group of the elastic pavement paving mixtures into test molds, tamp them, and then cure and form them to obtain several groups of specimens of elastic pavement paving mixtures; S6. Test the air void ratios of the several groups of specimens of elastic pavement paving mixtures, and determine the optimal powder-binder ratio of the filler and the polymer binder according to the air void ratios.
[0006] In an embodiment of the present invention, the particle size range of the rubber particles includes at least two of 9.5 - 4.75 mm, 4.75 - 2.36 mm, and 2.36 - 1.18 mm.
[0007] In an embodiment of the present invention, step S1 includes: Using the step-by-step filling method, mix rubber particles in the first particle size range and rubber particles in the second particle size range in different mass ratios, and then conduct a tamping density test to determine the minimum skeleton void ratio and the optimal mass ratio of the rubber particles in the first particle size range and the rubber particles in the second particle size range; Using the step-by-step filling method, mix the mixed rubber particles and rubber particles in the third particle size range in different mass ratios, and then conduct a tamping density test to determine the minimum skeleton void ratio and the optimal mass ratio of the mixed rubber particles and the rubber particles in the third particle size range, and obtain the optimal aggregate gradation of the rubber particles in the first particle size range, the rubber particles in the second particle size range, and the rubber particles in the third particle size range; where the mixed rubber particles are obtained by mixing the rubber particles in the first particle size range and the rubber particles in the second particle size range according to the optimal mass ratio.
[0008] In an embodiment of the present invention, step S2 includes: Dry the filler by heating until its weight remains constant, and cool the dried filler to room temperature; Stir the cooled filler and the polymer binder uniformly according to different powder-binder ratios to obtain several groups of binders.
[0009] In an embodiment of the present invention, the filler includes one or more of mineral powder and rubber powder; The polymer binder includes a thermosetting polymer with a curing time greater than 30 min.
[0010] In an embodiment of the present invention, the viscosity of the binder is 2 Pa·s to 30 Pa·s.
[0011] In an embodiment of the present invention, the mass ratio of the rubber aggregate, the filler, and the polymer binder satisfies the relationship: ; ; wherein, is the percentage of the rubber aggregate dosage, is the percentage of the filler dosage, is the percentage of the binder dosage, is the compacted density of the rubber aggregate, is the density of the filler, is the density of the binder, is the minimum skeleton void ratio of the rubber aggregate, is the target void ratio of the mixture.
[0012] In an embodiment of the present invention, the target void ratio of the mixture is 3% to 6%.
[0013] In an embodiment of the present invention, step S5 includes: Loading each group of the elastic pavement paving mixture into the test mold in batches, inserting a tamping knife along the periphery of the test mold for several times, inserting it in the middle of the test mold for several times and leveling the surface of the elastic pavement paving mixture, and then compressing the elastic pavement paving mixture to a preset specimen height with a counterweight block, and statically curing it at a preset temperature and a preset humidity until the elastic pavement paving mixture is cured to obtain an elastic pavement paving mixture specimen.
[0014] In an embodiment of the present invention, the calculation formula for the void ratio is: ; wherein, is the void ratio, is the bulk relative density of the elastic pavement paving mixture, is the maximum theoretical relative density of the elastic pavement paving mixture.
[0015] Compared with the prior art, the beneficial effects of the present invention: The mix proportion design method of the present invention uses rubber particles as the main aggregate. First, the optimal aggregate gradation of rubber particles in different particle size ranges is determined. Then, the mass ratios of rubber aggregate, polymer binder, and filler are determined by the main aggregate filling method combined with volume parameters. Considering the resilience of rubber particles, the mixture is tamped and then cured and formed to determine the optimal powder-binder ratio of the filler and the polymer binder, making the dense-graded elastic pavement paving design with rubber particles as the main aggregate follow certain rules, effectively guiding the preparation of elastic pavement paving mixture specimens, avoiding the problems of unqualified compaction degree and looseness of specimens caused by traditional design and forming methods, ensuring the uniformity of the mixture and the accurate achievement of the target void ratio. Compared with open-graded elastic pavement paving materials, it effectively improves the pavement durability and water stability, enriches the structural forms of elastic pavement materials, and is conducive to the further popularization of elastic pavement paving. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 FIG. is a schematic flow chart of a mix proportion design method for a dense-graded elastic pavement paving mixture provided by an embodiment of the present invention. DETAILED DESCRIPTION OF THE EMBODIMENTS
[0017] The following further describes the present invention in detail with reference to specific embodiments, but the implementation manners of the present invention are not limited thereto.
[0018] Please refer to Figure 1 , Figure 1 FIG., which is a schematic flow chart of a mix proportion design method for a dense-graded elastic pavement paving mixture provided by an embodiment of the present invention. The design method includes the following steps: S1. Mix rubber particles in different particle size ranges according to different mass ratios and conduct a tamping density test to determine the minimum skeleton gap ratio and the optimal mass ratio between rubber particles in different particle size ranges, and obtain the optimal aggregate gradation of rubber particles in different particle size ranges.
[0019] Specifically, first, using the step-by-step filling method, mix rubber particles in the first particle size range and rubber particles in the second particle size range according to different mass ratios and conduct a tamping density test to determine the minimum skeleton gap ratio and the optimal mass ratio between rubber particles in the first particle size range and rubber particles in the second particle size range. The minimum skeleton gap ratio and the optimal mass ratio can be used as the optimal aggregate gradation of rubber particles in the first particle size range and rubber particles in the second particle size range. Then, obtain mixed rubber particles by mixing rubber particles in the first particle size range and rubber particles in the second particle size range according to the optimal mass ratio. Using the step-by-step filling method, mix the mixed rubber particles and rubber particles in the third particle size range according to different mass ratios and conduct a tamping density test to determine the minimum skeleton gap ratio and the optimal mass ratio between the mixed rubber particles and rubber particles in the third particle size range, and obtain the optimal aggregate gradation of rubber particles in the first particle size range, rubber particles in the second particle size range, and rubber particles in the third particle size range.
[0020] Specifically, the particle size range of the rubber particles includes at least two of 9.5 - 4.75 mm, 4.75 - 2.36 mm, and 2.36 - 1.18 mm.
[0021] Exemplarily, first, conduct the tamping density test on the rubber particles with a particle size range of 9.5 - 4.75 mm and 4.75 - 2.36 mm according to the mass ratios of 9:1, 8:2, 7:3, 6:4, 5:5, 4:6, 3:7, 2:8. Each test can determine the natural bulk density, tamping density, natural void ratio, and tamping void ratio at the current mass ratio. Compare the tamping void ratios of all mass ratios, and take the minimum tamping void ratio and its mass ratio as the minimum skeleton clearance ratio and the optimal mass ratio of the rubber particles with a particle size range of 9.5 - 4.75 mm and 4.75 - 2.36 mm. Then, mix the rubber particles with a particle size range of 9.5 - 4.75 mm and 4.75 - 2.36 mm according to the optimal mass ratio to obtain mixed rubber particles. Conduct the tamping density test on the mixed rubber particles and the rubber particles with a particle size range of 2.36 - 1.18 mm according to the mass ratios of 10:0.6, 10:1.2, 10:1.8, 10:2.4, 10:3, 10:3.6, 10:4.2, 10:4.8. Determine the natural bulk density, tamping density, natural void ratio, and tamping void ratio at each mass ratio. Compare the tamping void ratios of all mass ratios, and take the minimum tamping void ratio and its mass ratio as the minimum skeleton clearance ratio and the optimal mass ratio of the mixed rubber particles and the rubber particles with a particle size range of 2.36 - 1.18 mm, so as to obtain the optimal aggregate gradation of the rubber particles with particle sizes of 9.5 - 4.75 mm, 4.75 - 2.36 mm, and 2.36 - 1.18 mm.
[0022] S2. Stir the filler and the polymer binder evenly according to different powder - binder ratios to obtain several groups of binders.
[0023] Specifically, dry the filler by heating until the weight of the filler remains constant, and cool the dried filler to room temperature. Stir the cooled filler and the polymer binder evenly according to different powder - binder ratios to obtain several groups of binders; Exemplarily, use a stirring device to stir the filler and the polymer binder with 3 - 4 different powder - rubber ratios evenly to obtain 3 - 4 groups of binders.
[0024] Specifically, the filler includes one or more of mineral powder and rubber powder. Among them, the mineral powder includes limestone powder, cement powder, silica powder, cement active powder, etc.; the rubber powder includes tire rubber powder and rubber powder made from other non - tire rubbers.
[0025] Specifically, the polymer binder includes thermosetting polymers with a curing time greater than 30 min, including epoxy resin-based thermosetting polymers, phenolic resin-based thermosetting polymers, unsaturated polyester resin-based thermosetting polymers, polyurethane-based thermosetting polymers, etc. Taking epoxy resin-based thermosetting polymers as an example, its main components include thermosetting epoxy resin and curing agent. Among them, the thermosetting epoxy resin includes epoxy resins cured at low temperature, epoxy resins cured at medium temperature, and epoxy resins cured at high temperature. Among them, the curing temperature of the epoxy resin cured at low temperature is -10~30 °C, and aliphatic amines (such as ethylenediamine), modified amine curing agents, etc. can be used, and the curing time is usually 24~48 h; the curing temperature of the epoxy resin cured at medium temperature is 50~100 °C, and imidazole or anhydride curing agents (such as phthalic anhydride) can be used, and the curing time is 1~4 h; the curing temperature of the epoxy resin cured at high temperature is 100~180 °C, and aromatic amines (such as DDM) or dicyandiamide curing agents can be used, and the curing time is 30 min~2 h.
[0026] Furthermore, to ensure the workability during construction, the viscosity of the binder obtained by mixing the filler and the polymer binder should be maintained at 2 Pa·s~30 Pa·s.
[0027] S3. Using the main aggregate filling method, according to the sum of the volume of the binder, the volume of the filler, and the volume occupied by the target void ratio of the mixture being equal to the void volume of the aggregate skeleton, calculate the mass ratio of the rubber aggregate, the polymer binder, and the filler in the mixture with different powder-binder ratios. Among them, the void volume of the aggregate skeleton is calculated from the minimum skeleton void ratio.
[0028] Specifically, based on the main aggregate filling method (CAVF method) for the composition design of asphalt mixtures, convert the minimum skeleton void ratio between rubber particles with different particle size ranges in step S1 into the minimum skeleton void volume of the aggregate, so that the sum of the volume of the binder, the volume of the filler, and the volume occupied by the target void ratio of the mixture is equal to the minimum skeleton void volume of the aggregate, and calculate the mass ratio of the rubber aggregate, the polymer binder, and the filler in the mixture with different powder-binder ratios. Among them, the target void ratio of the mixture refers to the target void ratio of the dense-graded elastic pavement paving material obtained by mixing the rubber aggregate, the polymer binder, and the filler, and the value is 3%~6%.
[0029] Specifically, the mass ratio of the rubber aggregate, the filler, and the polymer binder satisfies the relationship: ; ; Among them, is the percentage of the rubber aggregate dosage (%); is the percentage of the filler dosage (%); is the percentage of the binder dosage (%); is the compacted density of rubber aggregate (g / cm 3 ), is the density of filler (g / cm 3 ), is the density of binder (g / cm 3 ), is the minimum skeleton void ratio of rubber aggregate (%), is the target void ratio of mixture (%).
[0030] S4. Mix the rubber particles with the optimal aggregate gradation and each group of binders evenly according to the mass ratio to obtain several groups of elastic pavement paving mixtures.
[0031] Specifically, dry the rubber particles with the optimal aggregate gradation until the weight remains constant, and after cooling the rubber particles to room temperature, use a mixing device to mix the rubber particles and binders with 3 - 4 different powder - to - binder ratios evenly respectively to obtain 3 - 4 groups of mixed elastic pavement paving mixtures.
[0032] S5. Fill several groups of elastic pavement paving mixtures into the test molds respectively, tamp them, and then cure and form them to obtain several groups of elastic pavement paving mixture specimens.
[0033] Specifically, fill each group of elastic pavement paving mixtures into the test molds in batches. The test molds can be cylindrical or square. Then, based on the interlocking and filling principle, fully consider the resilience of the rubber particles. Use a tamping knife to tamp along the periphery of the test mold several times, tamp in the middle of the test mold several times, and level the surface of the elastic pavement paving mixture. Then, use a weight block to compress the elastic pavement paving mixture to the preset specimen height, and cure it statically under the preset temperature and humidity until the mixture solidifies to obtain elastic pavement paving mixture specimens.
[0034] Furthermore, the total filling mass of the mixture is calculated according to the volume of the formed specimen.
[0035] Furthermore, the preset temperature and curing time of static curing are determined by the curing conditions of the polymer binder. That is, when the polymer binder is a low - temperature - curing epoxy resin, the preset temperature of static curing is - 10~30°C, and the curing time is 24~48h; when the polymer binder is a medium - temperature - curing epoxy resin, the preset temperature of static curing is 50~100°C, and the curing time is 1~4h; when the polymer binder is a high - temperature - curing epoxy resin, the preset temperature of static curing is 100~180°C, and the curing time is 30min~2h. The preset humidity of static curing is controlled at 40~70%.
[0036] S6. Test the void ratios of several groups of elastic pavement paving mixture specimens, and determine the optimal powder - to - binder ratio of the filler and the polymer binder according to the void ratios.
[0037] Specifically, for the void ratio test, refer to the "Test Procedures for Highway Asphalt and Asphalt Mixtures" (JTG E20-2011), specifically T0705-2011 Compaction Density Test of Asphalt Mixtures (Table Dry Method), to measure the bulk relative density of the elastic pavement paving mixture specimens. And the maximum theoretical relative density , and calculate the void ratio using the following formula : ; Wherein, is the void ratio (%), is the bulk relative density of the elastic pavement paving mixture (g / cm 3 ), is the maximum theoretical relative density of the elastic pavement paving mixture (g / cm 3 ).
[0038] Furthermore, after determining the optimal powder-bitumen ratio of the filler and the polymer binder, verify the basic properties of the elastic pavement paving mixture specimens corresponding to this optimal powder-bitumen ratio. The basic property tests refer to the "Test Procedures for Highway Asphalt and Asphalt Mixtures", conduct immersion flushing loss test, rutting test, and low-temperature bending test on the elastic pavement paving mixture, and use the immersion flushing loss rate, dynamic stability, and maximum flexural tensile strain as the basis for evaluating water stability, high-temperature stability, and low-temperature crack resistance.
[0039] Furthermore, mix rubber particles, fillers, and polymer binders in different particle size ranges according to the optimal aggregate gradation of rubber particles and the optimal powder-bitumen ratio of the filler and the polymer binder, and after ramming the mixture, carry out curing and forming to prepare a dense-graded elastic pavement paving mixture.
[0040] For the convenience of understanding the present invention, the following examples are listed. Those skilled in the art should understand that the said examples are only for helping to understand the present invention and should not be regarded as specific limitations on the present invention.
[0041] Example 1: Purchase waste tire rubber particles produced by Company A and prepare a dense-graded elastic pavement paving mixture with a target void ratio of 3%.
[0042] S1. Mix waste tire rubber particles in different particle size ranges according to different mass ratios and conduct a ramming density test. It is determined that when the mass ratio of rubber particles of 9.5~4.75mm:4.75~2.36mm:2.36~1.18mm is 10:15:6, the minimum rubber skeleton void ratio is 38.34%.
[0043] Specifically, first, rubber particles with a particle size range of 9.5 - 4.75 mm and 4.75 - 2.36 mm are subjected to a tamped density test according to mass ratios of 9:1, 8:2, 7:3, 6:4, 5:5, 4:6, 3:7, 2:8. Each test can determine the natural bulk density, tamped density, natural void ratio, and tamped void ratio at the current mass ratio, as shown in Table 1. It can be seen from Table 1 that when the mass ratio of 9.5 - 4.75 mm to 4.75 - 2.36 mm rubber particles is 4:6, the tamped void ratio is the smallest. Therefore, the minimum skeleton clearance ratio of 9.5 - 4.75 mm and 4.75 - 2.36 mm rubber particles is 41.25%, and the optimal mass ratio is 4:6.
[0044] Table 1
[0045] Then, rubber particles with a particle size range of 9.5 - 4.75 mm and 4.75 - 2.36 mm are mixed according to the optimal mass ratio of 4:6 to obtain mixed rubber particles. The mixed rubber particles and rubber particles with a particle size range of 2.36 - 1.18 mm are subjected to a tamped density test according to mass ratios of 10:0.6, 10:1.2, 10:1.8, 10:2.4, 10:3, 10:3.6, 10:4.2, 10:4.8, that is, the rubber particles of 9.5 - 4.75 mm, 4.75 - 2.36 mm, and 2.36 - 1.18 mm are subjected to a tamped density test according to mass ratios of 4:6:0.6, 4:6:1.2, 4:6:1.8, 4:6:2.4, 4:6:3, 4:6:3.6, 4:6:4.2, 4:6:4.8 to determine the natural bulk density, tamped density, natural void ratio, and tamped void ratio at each mass ratio, as shown in Table 2. It can be seen from Table 2 that when the mass ratio of 9.5 - 4.75 mm, 4.75 - 2.36 mm, and 2.36 - 1.18 mm rubber particles is 4:6:2.4, the tamped void ratio is the smallest. Therefore, the minimum skeleton clearance ratio of 9.5 - 4.75 mm, 4.75 - 2.36 mm, and 2.36 - 1.18 mm rubber particles is 38.34%, and the optimal mass ratio is 4:6:2.4 (i.e., 10:15:6).
[0046] Table 2
[0047] Therefore, it can be determined that the optimal mass ratio of 9.5 - 4.75 mm:4.75 - 2.36 mm:2.36 - 1.18 mm rubber particles is 10:15:6, and the minimum skeleton clearance ratio is 38.34%.
[0048] S2. Dry the limestone powder by heating until its weight remains constant, then cool it to room temperature. Next, use a stirring device to evenly stir the limestone powder with powder-to-binder ratios of 0.8, 1.1, 1.4, and 1.7 with a low-temperature curing epoxy resin-based binder. The low-temperature curing epoxy resin-based binder is composed of a thiol curing agent and bisphenol A epoxy resin, obtaining 4 groups of binders with different powder-to-binder ratios. Among them, the viscosities of the 4 groups of binders are 2.2 Pa·s, 3.9 Pa·s, 9.7 Pa·s, and 29.3 Pa·s respectively.
[0049] S3. Based on the main aggregate filling method (CAVF method) for asphalt mixture composition design, with a minimum rubber skeleton void ratio of 38.34%, a target void ratio of 3%, and a limestone powder density of 2.73 g / cm 3 , and a binder density of 1.14 g / cm 3 Substitute into the mass ratio relationship formula of rubber aggregate, filler, and polymer binder, and calculate the amounts of rubber aggregate, polymer binder, and filler in the mixtures with powder-to-binder ratios of 0.8, 1.1, 1.4, and 1.7 respectively. The results are shown in Table 3.
[0050] Table 3
[0051] S4. Dry the rubber particles with the best aggregate gradation until their weight remains constant. After cooling the rubber particles to room temperature, according to the mass ratios in Table 3, use a mixing device to evenly mix the rubber particles with the 4 groups of binders with different powder-to-binder ratios respectively, obtaining 4 groups of mixed elastic pavement paving mixtures.
[0052] S5. Pour each group of mixed elastic pavement paving mixtures into the test mold in 3 times and fix them with spacer blocks. Then, use a tamping knife to tamp along the periphery of the steel cylinder of the test mold 15 times and tamp in the middle of the test mold 10 times and level the surface of the mixture; finally, compress the mixture fixed with the test mold and spacer blocks to the required specimen height through a counterweight block, and statically press it at 30 °C for 24 h until the binder is completely cured, obtaining specimens of elastic pavement paving mixtures.
[0053] S6. Test the void ratio of the elastic pavement paving mixtures, and verify their water stability, high-temperature stability, and low-temperature crack resistance with reference to the "Specifications for Highway Asphalt and Asphalt Mixture Tests". The results are shown in Table 4.
[0054] Table 4
[0055] It can be seen from Table 4 that the best powder-to-binder ratio of limestone powder and epoxy resin-based binder is 1.4. At this time, the void ratio of the mixture is the smallest, and its basic performance meets the requirements of the "Specifications for Design of Highway Asphalt Pavement" (JTG D50-2017) for pavement materials.
[0056] Example 2: Purchase waste tire rubber particles produced by Company B and prepare a dense-graded elastic pavement paving mixture with a target void ratio of 6%.
[0057] S1. Mix waste tire rubber particles in different particle size ranges according to different mass ratios and conduct a compaction density test. It is determined that when the mass ratio of rubber particles with particle sizes of 9.5 - 4.75 mm : 4.75 - 2.36 mm : 2.36 - 1.18 mm is 6:14:7, the minimum rubber skeleton void ratio is 36.24%.
[0058] S2. Dry the limestone powder by heating until its weight remains constant, and then cool it to room temperature. Then, use a stirring device to uniformly stir limestone powder with powder-to-binder ratios of 0.8, 1.1, 1.4, and 1.7 with a low-temperature curing epoxy resin-based binder. The low-temperature curing epoxy resin-based binder is composed of a thiol curing agent and bisphenol A epoxy resin, obtaining 4 groups of binders with different powder-to-binder ratios. Among them, the viscosities of the 4 groups of binders are 2.2 Pa·s, 3.9 Pa·s, 9.7 Pa·s, and 29.3 Pa·s respectively.
[0059] S3. Based on the main aggregate filling method (CAVF method) for asphalt mixture composition design, substitute the minimum rubber skeleton void ratio of 36.24%, the target void ratio of 6%, the density of limestone powder of 2.73 g / cm 3 , and the binder density of 1.14 g / cm 3 into the mass ratio relationship formula of rubber aggregate, filler, and polymer binder, and calculate the amounts of rubber aggregate, polymer binder, and filler in the mixtures with powder-to-binder ratios of 0.8, 1.1, 1.4, and 1.7 respectively. The results are shown in Table 5.
[0060] Table 5
[0061] S4. Dry the rubber particles with the best aggregate gradation until their weight remains constant. After cooling the rubber particles to room temperature, according to the mass ratios in Table 5, use a mixing device to uniformly mix the rubber particles with the 4 groups of binders with different powder-to-binder ratios respectively, obtaining 4 groups of mixed elastic pavement paving mixtures.
[0062] S5. Load the mixed elastic pavement paving mixture into the test mold in 3 times and fix it with a spacer block. Then, use a bayonet to insert and tamp 15 times along the periphery of the steel cylinder of the test mold and 10 times in the middle of the test mold and level the surface of the mixture; finally, compress the mixture fixed with the test mold and spacer block to the required specimen height through a counterweight block, and statically press it at 30°C for 24 h until the binder is completely cured, obtaining an elastic pavement paving mixture specimen.
[0063] S6. Measure the void ratio of the elastic pavement paving mixture, and verify its water stability, high-temperature stability, and low-temperature crack resistance with reference to the "Test Regulations for Highway Asphalt and Asphalt Mixtures". The results are shown in Table 6.
[0064] Table 6
[0065] It can be seen from Table 6 that the optimal powder-binder ratio of limestone powder to epoxy resin is 1.4. At this time, the void ratio of the mixture is the smallest, and its basic performance meets the requirements of the "Design Specifications for Highway Asphalt Pavements" (JTG D50-2017) for pavement materials.
[0066] Comparative Example 1: The remaining steps are the same as those in Example 1. In step S2, the powder-binder ratio of the filler limestone powder to the epoxy resin-based binder is 0.5, and the viscosity of the binder is 0.6 Pa·s, resulting in serious segregation during the mixing in S4 and the forming in S5, and it is impossible to form a uniform specimen.
[0067] Comparative Example 2: The remaining steps are the same as those in Example 1. In step S5, the Marshall compaction method is used to form the specimen. During the compaction process, the rubber aggregate is compressed and rebounds, resulting in the void ratio of the mixture decreasing first and then increasing, so that part of the binder used to fill the void ratio is extruded, and the target void ratio cannot be achieved.
[0068] The mix design method of this embodiment uses rubber particles as the main aggregate in the gradation design. First, determine the optimal aggregate gradation of rubber particles in different particle size ranges, and then use the main aggregate filling method combined with volume parameters to determine the mass ratio of rubber aggregate, polymer binder, and filler. Based on the principle of interlocking and filling, fully consider the resilience of rubber particles, tamp the mixture and then cure and form it, so as to determine the optimal powder-binder ratio of filler and polymer binder, making the dense-graded elastic pavement paving design with rubber particles as the main aggregate follow rules, effectively guiding the preparation of elastic pavement paving mixture specimens, avoiding the problems of unqualified compaction degree and looseness of specimens caused by traditional design and forming methods, ensuring the uniformity of the mixture and the accurate achievement of the target void ratio. Compared with open-graded elastic pavement paving materials, it effectively improves the pavement durability and water stability, enriches the structural form of elastic pavement materials, and is conducive to the further promotion of elastic pavement paving.
[0069] The above content is a further detailed description of the present invention in combination with specific preferred embodiments. It cannot be determined that the specific implementation of the present invention is only limited to these descriptions. For those of ordinary skill in the technical field to which the present invention belongs, without departing from the concept of the present invention, several simple deductions or substitutions can still be made, and all should be regarded as belonging to the protection scope of the present invention.
Claims
1. A method for designing the proportion of a dense elastic pavement mixture, characterized in that: Includes steps: S1. Mix rubber particles of different particle size ranges at different mass ratios and conduct a tamping density test to determine the minimum skeleton gap ratio and the best mass ratio between rubber particles of different particle size ranges, and obtain the best aggregate gradation of rubber particles of different particle size ranges; S2, mixing the filler and the polymer binder evenly according to different powder-to-binder ratios to obtain several groups of binders; S3, using the main aggregate filling method, according to the volume of the binder, the volume of the filler and the volume occupied by the target void ratio of the mixture is equal to the void volume of the aggregate skeleton, calculate the mass ratio of the rubber aggregate, the polymer binder and the filler in the mixture with different powder-rubber ratios, wherein the void volume of the aggregate skeleton is calculated by the minimum skeleton void ratio; S4, mixing the rubber particles of the optimal aggregate gradation and each group of the binder evenly according to the mass ratio to obtain several groups of elastic road paving mixtures; S5, respectively loading the plurality of groups of elastic pavement mixtures into test molds, tamping them, and then curing and forming them, to obtain a plurality of groups of elastic pavement mixture specimens; S6. Testing the porosity of the plurality of groups of elastic pavement paving mixture specimens, and determining the optimal powder-to-rubber ratio of the filler and the polymer binder according to the porosity.
2. The method for designing the proportion of densely distributed elastic pavement mixture according to claim 1, characterized in that: The particle size range of the rubber particles includes at least two of 9.5-4.75 mm, 4.75-2.36 mm, and 2.36-1.18 mm.
3. The method for designing the proportion of densely distributed elastic pavement paving mixture according to claim 1, characterized in that: Step S1 includes: Using a step-by-step filling method, the rubber particles in the first particle size range and the rubber particles in the second particle size range are mixed at different mass ratios and then subjected to a tamping density test to determine the minimum skeleton gap ratio and the best mass ratio of the rubber particles in the first particle size range and the rubber particles in the second particle size range; The mixed rubber particles are mixed with the rubber particles in the third particle size range at different mass ratios by using a step-by-step filling method, and then a compaction density test is performed to determine the minimum skeleton gap ratio and the optimal mass ratio of the mixed rubber particles and the rubber particles in the third particle size range, and to obtain the optimal aggregate gradation of the rubber particles in the first particle size range, the rubber particles in the second particle size range, and the rubber particles in the third particle size range; wherein the mixed rubber particles are obtained by mixing the rubber particles in the first particle size range and the rubber particles in the second particle size range at the optimal mass ratio.
4. The method for designing the proportion of densely distributed elastic pavement paving mixture according to claim 1, characterized in that: Step S2 includes: Drying the filler by heating until the weight remains constant, and cooling the dried filler to room temperature; The cooled filler and the polymer binder are mixed evenly according to different powder-to-binder ratios to obtain several groups of binders.
5. The method for designing the proportion of densely distributed elastic pavement mixture according to claim 1, characterized in that: The filler includes one or more of mineral powder and rubber powder; The polymer binder includes a thermosetting polymer with a curing time greater than 30 minutes.
6. The method for designing the proportion of densely distributed elastic pavement paving mixture according to claim 1, characterized in that: The viscosity of the binder is 2Pa·s~30Pa·s.
7. The method for designing the proportion of densely distributed elastic pavement mixture according to claim 1, characterized in that: The mass ratio of the rubber aggregate, the filler, and the polymer binder satisfies the relationship: ; ; in, is the percentage of rubber aggregate usage, is the percentage of filler dosage, is the percentage of binder material, is the compacted density of rubber aggregate, is the packing density, is the density of the binder, is the minimum skeleton gap ratio of rubber aggregate, is the target void ratio of the mixture.
8. The method for designing the proportion of densely distributed elastic road paving mixture according to claim 1, characterized in that: The target void ratio of the mixture is 3% to 6%.
9. The method for designing the proportion of densely distributed elastic pavement mixture according to claim 1, characterized in that: Step S5 includes: Each group of the elastic pavement paving mixture is loaded into the test mold in batches, and a ramming knife is used to tamp the mixture several times along the periphery of the test mold and several times in the middle of the test mold to level the surface of the elastic pavement paving mixture. Thereafter, a counterweight is used to compress the elastic pavement paving mixture to a preset specimen height, and static pressure curing is performed at a preset temperature and preset humidity until the elastic pavement paving mixture is solidified to obtain an elastic pavement paving mixture specimen.
10. The method for designing the proportion of densely distributed elastic pavement mixture according to claim 1, characterized in that: The calculation formula of the void ratio is: ; in, is the void ratio, is the relative bulk density of the elastic pavement mixture, It is the maximum theoretical relative density of elastic pavement mixture.
Citation Information
Patent Citations
Method for determining composition ratio range of rubber particle asphaltum mixture
CN101161703A
Design optimization method for porous elastic pavement mixture
CN110261248A
Polyurethane highly-elastic porous mixture material composition design method based on acoustic-mechanical synergy
CN112979215A
Optimization method for grading of rubber particles in rubber cement stabilized macadam mixture
CN117430382A
Elastic paving material
JP2002021008A